Treatment strategies for relapse after CAR T-cell therapy in B cell lymphoma - Negishi, Shuto; Girsch, James H.; Siegler, Elizabeth L.; Bezerra, Evandro D.; Miyao, Kotaro; Sakemura, R. Leo (Frontiers in Pediatrics, 2024)
Clinical trials of anti-CD19 chimeric antigen receptor T (CART19) cell therapy have shown high overall response rates in patients with relapsed/refractory B-cell malignancies. CART19 cell therapy has been approved by the US Food and Drug Administration for patients who relapsed less than 12 months after initial therapy or who are refractory to first-line therapy. However, durable remission of CART19 cell therapy is still lacking, and 30-60% of patients will eventually relapse after CART19 infusion. In general, the prognosis of patients who relapse after CART19 cell therapy is poor, and various strategies to treat this patient population have been investigated extensively. CART19 failures can be broadly categorized by the emergence of either CD19-positive or CD19-negative lymphoma cells. If CD19 expression is preserved on the lymphoma cells, a second infusion of CART19 cells or reactivation of previously infused CART19 cells with immune checkpoint inhibitors can be considered. When patients develop CD19-negative relapse, targeting different antigens (e.g., CD20 or CD22) with CAR T cells, investigational chemotherapies, or hematopoietic stem cell transplantation are potential treatment options. However, salvage therapies for relapsed large B-cell lymphoma after CART19 cell therapy have not been fully explored and are conducted based on clinicians’ case-by-case decisions. In this review, we will focus on salvage therapies reported to date and discuss the management of relapsed/refractory large B-cell lymphomas after CART19 cell therapy.